OCCURRENCE AND DISTRIBUTIONAL RANGE OF MANGROVE VASCULAR FLORA OF CATANDUANES ISLAND, LUZON, PHILIPPINES - JIMMY TEVAR MASAGCA (BIOTROPIA, 2008)
Mangroves play very significant roles not only on the economic aspects but also on the ecological aspects as biobelting for tidal surges and tsunamis. The loss of human lives due to the deadly tsunamis in East Asia and the unabated destruction of coastal vegetation have resulted in a renewed focus on the mangrove resources. The purpose of this paper is to report the existing mangrove database of the typhoon-prone island province of Catanduanes in Luzon, Philippines which will be used as bases in determining the appropriate educational management initiatives of various sectors for mangrove rehabilitation and regeneration. A total of 37 species of mangrove vascular flora (13 species of major mangrove elements, 10 species of minor mangrove elements and 14 associated mangrove species) were identified in the island under study. Two species of the genus Avicennia (A. marina and A. officinalis) were noted in the island. The other genera (Bruguiera, Ceriops, Sonneratia and Rhizophora) are well distributed in the designated eco-zones. Nypa fruticans is the most important mangrove plant species and a member of the screwpine family (Pandanaceae), Pandanus tectorius which is an associated mangrove species is well-distributed all throughout the island.Key words: Mangroves, vascular flora, Catanduanes, Philippines, occurrence and distribution.